Anno, M. (2021). "Los viajes. Europa". Traductor: Gabriel Álvarez Martínez, Kalandraka. 64pp. - Escrig Aparicio, José Antonio (Ondina - Ondine, 2022)
MITSUMASA ANNO: JUEGO E IDILIO Reseña de José Antonio Escrig Aparicio, Anno, M. (2021). "Los viajes. Europa". Traductor: Gabriel Álvarez Martínez, Kalandraka. 64pp